1978
DOI: 10.1111/j.1748-1716.1978.tb06187.x
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and biochemical changes in human skeletal muscle with age in sedentary males, age 22–65 years

Abstract: Biopsies for histochemical and biochemical analyses were taken from the vastus lateralis muscle of 55 untrained, healthy male subjects from 22 to 65 years of age. Fibre type distribution changed towards a decrease in the percentage of type II fibres, both in type IIA and type IIB fibres, whereas type IIB/IIA fibre ratio and type IIC percentage did not change with increasing age. It was found that the type IIB/IIA fibre ratio was inversely related to type I fibres, i.e. subjects rich in type I fibres had a rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
235
3
7

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(270 citation statements)
references
References 24 publications
25
235
3
7
Order By: Relevance
“…In agreement with many other studies,34, 35, 36 we found that the type II fibres were 18% smaller in muscles from the older participants than from the younger participants, while no such atrophy was observed for type I fibres. However, the similar average size of all fibres pooled in the old and the young participants and the greater variation in type I fibre size in the older participants suggest that the atrophy of type II fibres was accompanied by a concomitant (compensatory) hypertrophy, although not significant, of some type I fibres.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with many other studies,34, 35, 36 we found that the type II fibres were 18% smaller in muscles from the older participants than from the younger participants, while no such atrophy was observed for type I fibres. However, the similar average size of all fibres pooled in the old and the young participants and the greater variation in type I fibre size in the older participants suggest that the atrophy of type II fibres was accompanied by a concomitant (compensatory) hypertrophy, although not significant, of some type I fibres.…”
Section: Discussionsupporting
confidence: 93%
“…Preferential atrophy and loss of fast‐twitch fibers increase the ratio of slow‐twitch fibers to total fibers in aging muscle (Deschenes, Gaertner, & O'Reilly, 2013; Larsson, Sjödin, & Karlsson, 1978). We performed slow myosin heavy chain (sMHC) staining on cross sections of soleus muscle and found that the percentage of sMHC+ fibers/total fibers increased in wild‐type mice from 10 to 20 months of age.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses from human muscle biopsy samples have consistently demonstrated that type II fibers are more susceptible to aging-related atrophy when compared to type I fibers [3,50]. Doherty [51] reported that the loss of type II fiber area was 20-50%, whereas type I area loss was much less (1-25%).…”
Section: Type II Muscle Fibers and Agingmentioning
confidence: 99%
“…Although this phenomenon is well documented in animal and human studies, the underlying mechanisms leading to sarcopenia remain to be fully elucidated. The contributing mechanism(s) leading to sarcopenia are multi-factorial and may include: denervation and reinnervation of motor units, especially within skeletal muscles composed of a high degree of type II muscle fibers [1][2][3]; an alteration in the hormonal milieu in which anabolic hormone concentrations progressively decline [4,5]; elevated concentrations of inflammatory mediators that are not only associated with disease states, but also occur in healthy older adults [6][7][8][9][10][11][12][13]; and myonuclear loss through apoptotic mechanisms [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%